Evaluating Cybersecurity Risks of Bulgaria’s Energy Sector: Focus on PV and HVAC-R - Vultchan Gueorgiev; Valentin Totev; Plamen Tsankov; Stoyan Stoyanov (Applied Sciences, 2025)
Photovoltaics with energy storage are the current trend in solar energy. Hybrid inverters are the backbone of low-power installations of this type. If a single installation is compromised, there are no significant security concerns. However, multiple devices can be targeted simultaneously. Taking into account their increasing share in the energy mix, distributed cyber-attacks against these devices can threaten grid stability. The Bulgarian electric power system has been analyzed in order to determine its development which is in line with EU-wide trends. It can be concluded that hybrid inverters are expected to grow rapidly in number and in installed power. The vulnerability of hybrid inverters to cyber-attacks has been analyzed, and the possible consequences for the energy system have been identified. The technology allows it to be used as a hybrid means of influence, and this aspect is poorly addressed in existing cybersecurity regulations. A risk assessment has been made, based on which measures to improve security have been proposed.